1991
DOI: 10.1093/oxfordjournals.aje.a115955
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Antioxidant Vitamins and Subsequent Cancer Mortality in the 12-Year Follow-up of the Prospective Basel Study

Abstract: Plasma antioxidant vitamins A, C, and E and carotene were measured in a group of 2,974 men participating in the third examination of the prospective Basel Study in 1971-1973. In 1985, the vital status and mortality of all participants were assessed. A total of 204 men had died from cancer, including 68 with bronchus cancer and 37 with gastrointestinal cancer (20 with stomach cancer and 17 with large bowel cancer excluding cancer of the rectum). Overall mortality from cancer was associated with low mean plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(77 citation statements)
references
References 0 publications
2
69
1
4
Order By: Relevance
“…Certain plasma carotenoids can be considered as biomarkers of intake of fruits and vegetables (Al Delaimy et al, 2005a, b). Some earlier studies in Western populations (Willett et al, 1984;Stahelin et al, 1991) and more recent ones in high-risk Chinese populations Taylor et al, 2003;Yuan et al, 2004) show a higher GC risk in those with lower blood levels of some carotenoids or retinol. In contrast, some recent studies show a positive association between blood a-tocopherol levels and risk of GCs of the stomach cardia (Nouraie et al, 2005) and noncardial regions as well as the progression of dysplastic lesions to GCs (You et al, 2000).…”
mentioning
confidence: 88%
“…Certain plasma carotenoids can be considered as biomarkers of intake of fruits and vegetables (Al Delaimy et al, 2005a, b). Some earlier studies in Western populations (Willett et al, 1984;Stahelin et al, 1991) and more recent ones in high-risk Chinese populations Taylor et al, 2003;Yuan et al, 2004) show a higher GC risk in those with lower blood levels of some carotenoids or retinol. In contrast, some recent studies show a positive association between blood a-tocopherol levels and risk of GCs of the stomach cardia (Nouraie et al, 2005) and noncardial regions as well as the progression of dysplastic lesions to GCs (You et al, 2000).…”
mentioning
confidence: 88%
“…This conclusion is based on 1 of 2 cohort studies and 12 of 13 case-control studies showing inverse associations between dietary vitamin C intake and the risk of gastric cancer. In addition, one prospective study showed that baseline plasma vitamin C levels among subjects who died from gastric cancer (n = 20) was 20% lower than those who remained cancer-free (n = 2421) during more than 12 years of follow-up [43].…”
Section: Vitamin C (Ascorbic Acid)mentioning
confidence: 99%
“…Vitamin E is an essential micronutrient which may have protective effects against cardiovascular diseases and several cancers through different biological mechanisms (Grant & De Hoog, 1985;Willett, 1986;Diplock, 1991;Stahelin et al, 1991;Ashwell, 1993;Rimm et al, 1993;Stampfer et al, 1993;Bellizzi et al, 1994;Kushi et al, 1996). It has antioxidant properties, which may prevent cellular damage (Bieri, 1984;Ames, 1983).…”
Section: Introductionmentioning
confidence: 99%